Factors Related To Event DHF In Children In Mawar Care - Haerani; Haerati; Bau Ranti (Jurnal Life Birth, 2019)
DHF is an acute epidemic disease caused by a virus transmitted by Aedes Aegepty. According to 2014 World Health Organization (WHO) data, Dengue Hemorrhagic Fever was first reported in Southeast Asia in 1954 in the Philippines, then spread to various countries. Before 1970 only 9 countries experienced DHF outbreaks, but now DHF has become an endemic disease in more than 100 countries, including Africa, America, Eastern Mediterranean, Southeast Asia and the Western Pacific which have the highest number of DHF cases. The purpose of this study is to know the factors associated with the incidence of DHF in children in the Mawar Care Room of RSUD H.Andi Sulthan Daeng Radja Bulukumba in 2018. The method used in this study is analytical method. The sample in this study amounted to 162 people using total sampling. Retrieval of secondary data. Analysis of the data used by using the chi-square test. This research was conducted using the chi-square test with a level of confidence (Î± = 0.05) and the value of p-value = 0,000 was obtained, meaning p <Î± (0,000 <0.05). There is a relationship between the incidence of DHF in children in the Mawar Care Room of H.Andi Sulthan Daeng Radja Bulukumba Hospital. It is recommended that hospital institutions continue to provide information about factors related to the incidence of DHF.